Description of a new species of Mauroniscus Bourgeois, 1911 from Chile (Coleoptera: Mauroniscidae) - Estrada, Patricia; Solervicens, Jaime (Zootaxa, 2021)
A new species of Mauroniscus Bourgeois, 1911, Mauroniscus chilensis n. sp., from central Chile is described using external characters of the adult male and female including terminal segments of the abdomen and genitalia. The morphological differences of Mauroniscus chilensis n. sp. with M. maculatum Pic, 1927 are discussed